استخدام برنامج "العربية على الإنترنت" arabic.seu.edu.saلتعليم مهارة الاستماع في المدرسة الثانوية الإسلامية الحكومية الثالثة : Online Arabic Program, Learning Listening Skills - Amalina, Rabiyana; Arifin, Ahmad; Hakim, Arif Rahman (Tarbiyah : Jurnal Ilmiah Kependidikan, 2024)
Mastering Arabic requires strong listening skills as a foundational element. The research problem is whether the use of an online Arabic program for teaching listening skills in grade X at MAN 3 Banjarmasin is effective. The objective of this study is to determine the effectiveness of using an online Arabic program for teaching listening skills in grade X at MAN 3 Banjarmasin. The research employs a quasi-experimental approach with Nonequivalent Control Group design, focusing on the effectiveness of the online Arabic program in enhancing listening skills among tenth-grade students at MAN 3 Banjarmasin. The findings indicate that the utilization of this program yields positive results, evidenced by the post-test average scores: 85.63 for the experimental class and 78.13 for the control class. With a Sig value of 0.002, which is less than 0.05, Ha is accepted, indicating that the online Arabic program is effective in teaching listening skills at MAN 3 Banjarmasin.